The physics of oil outflow from crude oil tankers during ship-ship collisions - Qu, Guan Lin (2016)
The consequences caused by tanker collisions have become one of the main sources of oil pollution. Therefore this project is brought out to study on the physics of oil outflow from crude oil tankers during ship-ship collisions. The main aim of this paper is to find out the amount of oil outflow and factors that affected.